Differential Effects of Canonical Androgens and 11-Ketotestosterone on Reproductive Phenotypes and Folliculogenesis in Mouse Model of PCOS - Yi-Ru Tsai; Yen-Nung Liao; Cheng-Ju Tsai; Yu-Ang Lee; Shih-Min Hsia; Kuo-Chung Lan; Hong-Yo Kang (Biomedicines)
Background: Polycystic ovary syndrome (PCOS) is a common female endocrine disorder characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. While canonical androgens like testosterone (T) and dihydrotestosterone (DHT) are well studied in PCOS pathophysiology, the role of 11-ketotestosterone (11KT) remains unclear. This study investigates the differential effects of these androgens on folliculogenesis, ovulation, and steroidogenesis using in vivo and in vitro models. Methods: Four-week-old female C57BL/6 mice received T, DHT, or 11KT for six weeks. The assessments included body weight, estrous cyclicity, serum hormone profiles, ovarian histology, and follicle classification. In parallel, large preantral follicles were cultured with each androgen to evaluate follicle growth, antrum formation, and ovulation capacity. Androgen receptor (AR) signaling and steroidogenic function were analyzed using western blotting, RT-qPCR, and luciferase reporter assays. Results: The DHT-treated mice exhibited increased weight gain, whereas 11KT-treated mice showed reduced weight gain. T and DHT disrupted the estrous cycle, while 11KT prolonged diestrus. All androgen treatments led to ovarian morphological changes, including follicular arrest and cystic features. In vitro, all androgens enhanced follicle growth, but only T and DHT inhibited ovulation. The AR expression was elevated across all androgen-treated groups, but only DHT significantly activated AR and CYP19A1 promoters. Conclusions: 11KT induces a distinct and milder PCOS-like phenotype compared to classical androgens, promoting follicle growth with minimal impact on ovulation or steroidogenic disruption. These findings underscore the heterogeneity of PCOS and suggest that different androgen profiles may drive diverse clinical phenotypes. By elucidating the distinct roles of different androgens, this may lead to better stratification of PCOS phenotypes based on predominant androgen types for more precise diagnosis and individualized management.